Effect of flame retardant fillers on the rheological properties of composite materials of ethylene-vinyl acetate copolymer - Chulieieva, Olena (Eastern-European Journal of Enterprise Technologies, 2017)
We determined that viscous flow processes are influenced by composite materials of ethylene-vinyl acetate copolymer that do not sustain combustion and by flame retardant fillers. In the study, ethylene-vinyl acetate copolymer was used. The content of vinyl acetate is 18 % and 28 %; MFI is 2.5 g/10 min or 5 g/10 min. Flame retardant fillers include aluminum oxide trihydrates with an average diameter of particles of 1.5 µm and 3.0 µm; magnesium oxide dihydrates with an average diameter of particles of 3.0 μm and 3.7 μm and hydromagnesite with an average diameter of particles of 1.4 μm. By using the method of capillary viscosimetry, we defined the following characteristics: melt flow index, shear stress, shear rate, effective viscosity and activation energy of viscous flow. Melt flow index decreases as the concentration of flame retardant fillers increases. The same tendency is observed when using flame retardant fillers with smaller average diameter of particles. Shear stress and effective viscosity, in contrast, increase. We determined the influence of polymeric matrix, composition and dispersion of flame retardant fillers on the rheological characteristics of polymeric compositions. The use of EVA with melt flow index of 5 g/10 min makes it possible to obtain the filled polymeric compositions with improved rheological properties. The obtained results might be useful in the process of designing the formulations for polymeric compositions for cable products and for regulating technological indicators during their processing.